2019
DOI: 10.1155/2019/2498916
|View full text |Cite
|
Sign up to set email alerts
|

A Stress-Strain Model for Unconfined Concrete in Compression considering the Size Effect

Abstract: In this study, a stress-strain model for unconfined concrete with the consideration of the size effect was proposed. The compressive strength model that is based on the function of specimen width and aspect ratio was used for determining the maximum stress. In addition, in stress-strain relationship, a strain at the maximum stress was formulated as a function of compressive strength considering the size effect using the nonlinear regression analysis of data records compiled from a wide variety of specimens. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(101 reference statements)
1
3
0
Order By: Relevance
“…Its testing result proved to be aberrant. In general, the samples showed failure patterns in unconfined compression that are similar to that of concrete as documented by Yang et al (2019), indicating that the use of BTS and UPT, which are suitable for concrete materials, can be justified. were used by Liu, et al (2018).…”
Section: Ucs Testing Resultssupporting
confidence: 55%
“…Its testing result proved to be aberrant. In general, the samples showed failure patterns in unconfined compression that are similar to that of concrete as documented by Yang et al (2019), indicating that the use of BTS and UPT, which are suitable for concrete materials, can be justified. were used by Liu, et al (2018).…”
Section: Ucs Testing Resultssupporting
confidence: 55%
“…For the case of AC columns, the experimental and analytical studies conducted by Refs. [33][34][35][36][37][38] evidenced that ε c0 increases with the concrete compressive strength (f c0 ). Jansen and Shah [34] experimentally demonstrated that the column aspect ratio (λ L as the ratio of the column height to its diameter) has also considerable influence on ε c0 due to the occurrence of strain-localization within a finite zone with a pronounced gradient of deformations due to the concrete post-peak strain-softening behavior.…”
Section: Axial Strain At the Peak Stage Of Ac Columns (ε C0 )mentioning
confidence: 99%
“…In this study, in order to estimate ε c0 , a large database (Table 3) was compiled from the experimental results available in the literature, resulting in 604 unconfined concrete specimens (AC) with a broad range of concrete properties and geometry configurations. Note that for the case of non-circular columns with a total cross-section area of A g , based on Yang et al [38] recommendations, λ L can be determined as L/d eq where L is the columns' height and d eq is the equivalent circular ]). Based on a preliminary sensitivity analysis, a low effect was achieved for the influence of the column size (i.e.…”
Section: Axial Strain At the Peak Stage Of Ac Columns (ε C0 )mentioning
confidence: 99%
“…As a result, by calculating f ctr,T , ε ctr,T , f cu,T and ε cu,T using Eqs. (35), 34,21,30), the information of the key components of the proposed stress-strain model can be addressed.…”
Section: Sub-models For Transition Point (ε Ctrt F Ctrt ) At Elevate...mentioning
confidence: 99%